Severe anemia and adverse pregnancy outcome in a tertiary care hospital in North India - Yadav, Premlata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia is commonest medical disorder in pregnancy with 88% prevalence in India mainly due to ignorance, poverty and gender bias. 40-60% of maternal deaths in developing countries. According to the recent standard laid down by WHO anemia is present when the hemoglobin (Hb) concentration in the peripheral blood is less than 11 gm/dl. The most common cause of anemia in pregnancy is iron deficiency. Anemia is diagnosed by estimating the hemoglobin concentration and examining a peripheral blood smear for the characteristic red blood cell changes. The aim of the study was to determine the association between severe anemia, maternal and perinatal complications. Methods: Case control study was done in department of Obstetrics and Gynecology, Rajendra Institute of Medical Sciences Ranchi, India from February 2016 to July 2016. 100 pregnant women, admitted for delivery and having severe anemia were studied and compared with 100 non-anaemic women of similar demographic features. Maternal and perinatal complications were observed. Pearson, chi-square and Fischer exact tests were used to calculate significance of results. Results: Of the severely anaemic mothers, 36% babies were low birth weight (p=0.042) and 20% were small for gestational age (p = 0.026), as compared to 18% and 10% of controls, respectively. Conclusions: Severe maternal anemia carries significant risk of hemorrhage and infection in the mother. It is also associated with preterm birth, low birth weight.